A hydrolysis-hydrothermal route for the synthesis of ultrathin LiAlO2-inlaid LiNi0.5Co0.2Mn0.3O2 as a high-performance cathode material for lithium ion batteries. Issue 1 (25th November 2014) - Li, Lingjun; Chen, Zhaoyong; Zhang, Qiaobao; Xu, Ming; Zhou, Xiang; Zhu, Huali; Zhang, Kaili
Abstract : Lithium residues on the surface of LiNi0.5 Co0.2 Mn0.3 O2 have been removed as raw materials to synthesize LiAlO2 -inlaid LiNi0.5 Co0.2 Mn0.3 O2 cathode materials in situ for lithium ion batteries. Abstract : We present a novel hydrolysis-hydrothermal approach to using lithium residues on the surface of LiNi0.5 Co0.2 Mn0.3 O2 as raw materials to synthesize ultrathin LiAlO2 -inlaid LiNi0.5 Co0.2 Mn0.3 O2 cathode materials, for the first time. High-resolution transmission electron microscopy (HRTEM) and fast Fourier transform (FFT) analysis indicate that the spherical particles of LiNi0.5 Co0.2 Mn0.3 O2 are completely coated by crystalline LiAlO2 with an average thickness of 4 nm; cross-section SEM and corresponding EDS results confirm that partial Al 3+ ions are doped into the bulk LiNi0.5 Co0.2 Mn0.3 O2 with gradient distribution. Electrochemical tests show that the modified materials exhibit excellent reversible capacity, enhanced cyclability and rate properties, combining with higher Li ion diffusion coefficient and better differential capacity profiles compared with those of the pristine material. Particularly, the 2 mol% LiAlO2 -inlaid sample maintains 202 mA h g −1 with 91% capacity retention after 100 high-voltage cycles (with 4.6 V charge cut-off) at 1 C. The enhanced electrochemical performance can be ascribed to the removal of lithium residues and the unique LiAlO2 -inlaid architecture. The removal of lithium residues are believed to decrease side reactions between Li2 O and the electrolyte, while the unique LiAlO2 -inlaid architecture can buffer the volume change of core and shell during cycles, enhance the composite's lithium ion diffusion ability and inherit the advantages of LiAlO2 coating and doping.